GAMBARAN FAKTOR RISIKO STROKE PADA PASIEN STROKE DI POLIKLINIK SARAF RSUD INDRAMAYU - Riyanto Riyanto; Siti Nuraisyah (JURNAL KESEHATAN INDRA HUSADA, 2017)
Stroke is one of the main causes of death and neurological disability in Indonesia and is a medical emergency that must be handled promptly, precisely, and meticulously. This study aims to determine the description of stroke risk factors in stroke patients in polyclinic nerve of regional public hospital 2017. This type of research is quantitative with the research method used is descriptive method. Population in this study were all stroke patients who underwent treatment at polyclinic nerve of regional public hospital Indramayu and sampling using quota sampling so that got sample which amounted to 67 respondents. The result of research shows the highest percentage for age is as many as 35(52,2%) respondents aged 57 years, female 35 (52,2%) respondents, had family history of disease 56 (83,6%) respondents, all the respondent (100%) had a history of hypertension, 42 (62,7%) had a history of diabetes mellitus, had no a history of heart disease 66 (98,5%) respondents, and 35 (52,2%) respondents never smoked.